Expert System For Cupping Treatment Using Case Based Reasoning Method - Evi Dewi Sri Mulyani; Rahadi Deli Saputra; Rais Mujahidul Haq (Universitas Raharja, 2020)
Cupping is one of the methods of treatment taught by Rasulullah SAW (thibbun nabawi) which can be believed to be a cure because it is sourced from revelations that are certain, divine powers with the perfection of reason. Rasulullah SAW said: